Seguimiento académico en el fortalecimiento de competencias de saberes en los estudiantes de la básica primaria (2019)
The competences of knowledge in the student are strengthened by the teachers to the extent that a process of academic follow-up is carried out, in which students are identified who in the construction of knowledge present difficulties for their true learning. From this point of view, this research seeks to analyze a situation of low academic performance of students, based on an empiricist approach and positivist paradigm through a quantitative research design, developed in two stages: theoretical and field. The population is made up of 104 boys and girls, with a sample of 30 children from grades 5 of the primary basic education of the Francisco José de Caldas educational institution in Costa Hermosa. The technique of documentary observation and analysis was used on an institutional virtual platform.